"Single-minded, compelling, and unique": visual communications, landscape, and the calculated aesthetic of place branding - Porter, Nicole (Taylor and Francis, 2013)
Place branding strategies play a significant role in the professional composition of landscape imagery, including the depiction of “natural” landscapes. In this paper, Brand Blue Mountains, a brand currently implemented in the Blue Mountains region (Australia), is discursively analyzed. The brand sets out an all-encompassing “Vision” defining the identity, values and personality of the World Heritage listed Blue Mountains landscape, summarized in the tagline Elevate Your Senses. This “vision” is visually translated into a strictly coordinated and copyrighted suite of logos, graphic design, color, fonts and various photographic styles. Analysis reveals that the degree of control that place brand strategists seek to exert over the visual expression of landscape identity is significant. A highly selective narrative of positive nature-based sensory experience is constructed through the holistic application of contemporary visual media. The brands' communications strategy naturalizes and reinforces a particular market-friendly version of place. The framework that brands set for the representation of landscapes overall amounts to an exercise in calculated aesthetics, whereby the form and content of landscape images of various kinds is measured to achieve the greatest market differentiation and impact which technologies allow. The result of this calculated aesthetic system, with its taglines, saturated color, careful composition and magazine-format brevity, is a reduction in the complexity of landscape representations and a perpetuation of nature stereotypes.